Integrating Green Skills into TVET Curricula in Polytechnics Malaysia - Chee Sern , Lai; Baharom, Noordiana; Ming Foong, Lee; Wan Muda, Wan Hanim Nadrah; Rosli, D'oria Islamiah; A., Ana (Journal of Technical Education and Training, 2021)
Green skills are very much needed by green industry. Nevertheless, many TVET institutions have not yet embedded green skill elements into the programme's curriculum because it is still unclear concerning the types of green skills demanded by the green industry. Therefore, this research was conducted to identify the green skills that should be integrated into TVET curricula from the perspective of engineering lecturers in Polytechnics. The nature of this research was descriptive in which the date were collected using self-developed questionnaire. Four Polytechnics located in the East Coast, Northern, Central, and Southern of Malaysia were involved. A total of 332 engineering lecturers from three departments of engineering (Civil, Electrical, and Mechanical Engineering) were invited to participate in this research. The findings revealed that the TVET curricular should contains some of these green skills: problem solving skill related to environmental pollution,  interpretative skill on environmental phenomena, research skill on environmental issues, data collection skill, analytical skill, exploitation skill on green technology, management skill on natural resources, design skill, controlling skill on environment pollution, raw material management skill, energy saving skill, recycling skill, and reuse skill. It is suggested that Polytechnics should embed these green skills into their programme curricula in order to produce graduates who are able to meet the needs of green industry.